The Role of Intermediary in Sustainable Lending: An Economic Analysis of Crowdfunding Platform - GE, Ling (Institutional Knowledge at Singapore Management University, 2015)
Is the interest-free crowdfunding platform a promising alternative to the non-zero interest platform? This study investigates the lenders and borrowers’ incentives and choices between an indirect, non-zero interest rate platform intermediated by a field partner and a direct-lending, interest-free platform. We model the field partner as a profit maximizer that filters qualified borrowers to enable the lenders’ capital to be better utilized on the crowdfunding platform. We show that, under certain conditions, both the borrowers and lenders are better off from the existence of the field partner. The existence of field partner is necessary to effectively segment the market and improve social welfare.